2019
DOI: 10.3390/ijms20163950
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of LncRNA Reveals the Temporal-Specific Module of Goat Skeletal Muscle Development

Abstract: A series of complex processes regulate muscle development, and lncRNAs play essential roles in the regulation of skeletal myogenesis. Using RNA sequencing, we profiled the lncRNA expression during goat (Capra hircus) skeletal muscle development, which included seven stages across fetal 45 (F45), 65 (F65), 90 (F90), 120 (F120), 135 (F135) days, born for 24 h (B1) and 90 (B90) days. A total of 15,079 lncRNAs were identified in the seven stages, and they were less conservative with other species (human, cow, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 60 publications
(49 reference statements)
7
26
0
Order By: Relevance
“…According to the present study, lncRNAs and mRNAs are expressed in a stage-dependent manner, consistent with previous studies [34][35][36]. The results of both hierarchical clustering and PCA showed that the GRI and MGI stages were more distinct than MGI and RSI stages at the mRNA or lncRNA level (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…According to the present study, lncRNAs and mRNAs are expressed in a stage-dependent manner, consistent with previous studies [34][35][36]. The results of both hierarchical clustering and PCA showed that the GRI and MGI stages were more distinct than MGI and RSI stages at the mRNA or lncRNA level (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Downregulated expression of the HDAC9 gene has been observed in callipyge animals relative to non-callipyge sheep[66] (Vuocolo et al, 2007). Furthermore, EYA2 was reported to be associated with muscle hypertrophy in goats[64] (Ling et al, 2019). From the genes mentioned here, LIG1 and STK38L were associated with BW in the Afrino population, while XIRP2 was linked to BW and TWW in the Grootfontein Merino population.…”
mentioning
confidence: 73%
“…Considering the knockdown of DICER1, we realized that the KEGG pathways of the downregulated mRNAs include PI3K-AKT signaling pathway [62], Focal adhesion [66], and ECM receptor interaction [66], which are also recognized to be associated with muscle development. Moreover, FoxO signaling pathway [66], MAPK signaling pathway [70], Rap1 signaling pathway [68,69], and mTOR signaling pathway [77] were also known to be associated with the upregulated miRNAs. Moreover, all these pathways are related to muscle development.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, Rap 1 is a small GTPase that regulates different processes, including tightening of cell-cell junction [68], cell polarity, and cell adhesion [69]. MAPK signaling pathway is indicated to regulate the regeneration and proliferation of muscle stem cells [70]. In addition, the MAPK signaling pathway plays a signi cant role during myoblast differentiation [71,72].…”
Section: Discussionmentioning
confidence: 99%